Da crítica à ontologia ao encontro com o outro na ética de Levinas - Soares, Davidson Marinho (2021)
The central purpose of our work is to understand the path of Levinas' criticism of ontology, as well as the way in which Levinasian philosophy overcomes ontology through ethics. Having as a guiding principle of our research the work Totality and Infinite (2019), but also when necessary, making references to the other works of Levinas and commentators. We aim to show how Levinasian philosophy finds the inclination of ontology to reduce the other to the same. This movement of thinking about the other, always in the register of the same, shapes what Levinas conceptualizes as totality. Such a perspective of thinking the other under the calculation of ontological reason is at the origin of philosophical thought. From classical philosophy with the first philosophers to contemporaneity with Husserl and Heidegger, the other was thought from the perspective of ontological primacy. In this sense, Levinas proposes to think of the other outside the arrangement of the totality and understanding of the same, therefore, he proposes ethics before ontology, and the other before it. For Emmanuel Levinas, the departure from ontology towards ethics as the first philosophy is only possible through the infinite expressed in the face of the other. It is in the pure expression of the other's face that the rupture with the totality occurs. It is in the face of the other, from the idea of the infinite, that he is summoned to ethical responsibility for the other's otherness.